2021
DOI: 10.1088/1742-6596/1835/1/012095
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Needs Assessment of Hyflex Learning with Science Activity Base For Strengthen Critical Thinking

Abstract: This article aimed to analyzed the factors of Hyflex learning with science activity base for strengthen critical thinking.This mixed method research on the qualitative research and quantitative research both to participatory action learning. The first to involved synthesizing documentary, interview with 20 teachers, and to collection data by questionnaire with 150 teachers and 150 students. The study revealed that the factors were to instructional using the students base, content transferal of technology to kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…HyFlex learning could be described as an optimum way of learning as the variety of instruction modalities can outperform fully online and traditional face-to-face classes. With a learner-centered focus (Beatty, 2007), Hyflex learning model depends on the needs and learning processes (Jongmuanwai et al, 2021); thus, it presents various benefits shown in Table 1.…”
Section: Benefits and Challenges Of Hyflexmentioning
confidence: 99%
“…HyFlex learning could be described as an optimum way of learning as the variety of instruction modalities can outperform fully online and traditional face-to-face classes. With a learner-centered focus (Beatty, 2007), Hyflex learning model depends on the needs and learning processes (Jongmuanwai et al, 2021); thus, it presents various benefits shown in Table 1.…”
Section: Benefits and Challenges Of Hyflexmentioning
confidence: 99%
“…36 The HyFlex learning is where a student has the choice to attend classes face-to-face in-person (synchronously), online (synchronously or asynchronously) and interchange the use of the two modalities (face-to-face and online) at will during a module. 37 In HyFlex learning, therefore, the students use face-to-face and online modalities in a complementary manner. The HyFlex modality is student-centred, enhances students' knowledge and clinical practice assessment, but a study has shown that practical skills acquisition may be better with face-toface learning than HyFlex simulation learning.…”
Section: Learning Types and Activitiesmentioning
confidence: 99%
“…This has implications for determining the content, strategy and choice of HyFlex learning modes that suit the needs of students (Mahande and Abdal, 2022; Mahande and Abdal, 2023). However, students should be able to choose a weekly HyFlex learning modality or each topic based on their needs and learning style (Jongmuanwai et al , 2021; Esteron, 2021) to create equity pedagogy.…”
Section: Introductionmentioning
confidence: 99%